Need Analysis of E-module Based on the Theory of Conceptual Change in Earth and Space Material for Class X of Vocational School in the Sumatra - Sri Hasih Nurhayati; Sardianto Markos Siahaan; Syuhendri (Postgraduate, University of Mataram, 2024)
This research examined the need for developing E-modules based on the Theory of Conceptual Change in physics education, with a focus on the topic of Earth and Space Sciences. Research method is quantitative descriptive The results of the questionnaire analysis involving teachers in 7 provinces, namely South Sumatra, West Sumatra, North Sumatra, Bengkulu, Jambi, Bangka Belitung Islands, Riau and students in 6 provinces, namely South Sumatra, West Sumatra, Bengkulu, Jambi, Bangka Belitung Islands, Riau shows that the average use of E-modules is still limited in schools, namely 42%, while an average of 70% of students stated that they had difficulty understanding physics concepts, especially those related to Earth and Space Sciences. Therefore, 100% of teachers and 88% of students agree that the development of E-modules based on Conceptual Change Theory needs need to do.